Analisis Asuhan Keperawatan Penurunan Curah Jantung Pada Pasien Congestive Heart Failure (CHF) - Rahmawati ibrahim; Fadli Syamsuddin (Pusat Riset dan Inovasi Nasional, 2023)
Congestive heart failure (CHF) is a clinical syndrome (a collection of signs and symptoms) characterized by dyspnea and fatigue (at rest or during activity) due to abnormalities in the structure and function of the heart. CHF can be caused by diseases that cause reduced ventricular filling (diastolic dysfunction) and/or myocardial contraction (systolic dysfunction). The purpose of this study is so that the authors are able to perform Nursing Care for Decreased Cardiac Output in Congestive Heart Failure (CHF) Patients. used is a case study, this research is descriptive in the form of a case report which is a nursing analysis. This research was conducted from 26 December 2022 - 07 January 2023, with a total sample of 3 respondents. The case data showed that the three patients had a history of hypertension, 1 patient with a history of Diabetes Mellitus, 2 patients had a Medical Diagnosis of Congestive Heart Failure (CHF) and 1 patient had a Medical Diagnosis of Hypertensive Heart Disease (HHD). The three patients had the same cardiac EKG, namely Arrhythmia, 2 patients had results of Photo Thorax Cardiomegaly and All patients had a weak general condition with Composmentis awareness. With the appointment of a nursing diagnosis of Decreased Cardiac Output. The three patients had a history of the same disease, namely hypertension and 1 patient had diabetes mellitus and used the nursing diagnosis of decreased cardiac output.